STUDI KEANEKARAGAMAN BAKTERI DALAM SALURAN PENCERNAAN SEMUT GENUS SEMUT GENUS SEMUT GENUS SEMUT GENUS C A M P O N O T U S C A M P O N O T U S C A M P O N O T U S C A M P O N O T U S : : : : SEBUAH ANALISIS BERDASARKAN SEBUAH ANALISIS BERDASARKAN SEBUAH ANALISIS BERDASARKAN SEBUAH ANALISIS BERDASARKAN JENIS MAKANAN SEMUT JENIS MAKANAN SEMUT JENIS MAKANAN SEMUT JENIS MAKANAN SEMUT - St Wahidah Arsyad (Universitas Lambung Mangkurat, 2004)
This research aims to express the diversity of bacteria in digestion channel of ants, study the interation between bacteria and ants, and the existence of bacteria degrades celules base on the kind of ant food. This research is done with exsplorative – survei - description of bacteria in digestion channel of ant. This research is succesful to find out six kind of bacteria of ants genus C a m p o n o t u s. From six kind of bacteria, one of them are able to degrade celulosa.